DWI of Prostate Cancer: Optimal b-Value in Clinical Practice. (17th February 2014) - Manenti, Guglielmo; Nezzo, Marco; Chegai, Fabrizio; Vasili, Erald; Bonanno, Elena; Simonetti, Giovanni
Abstract : Aim . To compare the diagnostic performance of diffusion weighted imaging (DWI) using b -values of 1000 s/mm 2 and 2000 s/mm 2 at 3 Tesla (T) for the evaluation of clinically significant prostate cancer. Matherials and Methods . Seventy-eight prostate cancer patients underwent a 3T MRI scan followed by radical prostatectomy. DWI was performed using b -values of 0, 1000, and 2000 s/mm 2 and qualitatively analysed by two radiologists. ADC maps were obtained at b -values of 1000 and 2000 s/mm 2 and quantitatively analyzed in consensus. Results . For diagnosis of 78 prostate cancers the accuracy of DWI for the young reader was significantly greater at b = 2000 s/mm 2 for the peripheral zone (PZ) but not for the transitional zone (TZ). For the experienced reader, DWI did not show significant differences in accuracy between b -values of 1000 and 2000 s/mm 2 . The quantitative analysis in the PZ and TZ was substantially superimposable between the two b -values, albeit with a higher accuracy with a b -value of 2000 s/mm 2 . Conclusions . With a b -value of 2000 s/mm 2 at 3T both readers differentiated clinical significant cancer from benign tissue; higher b -values can be helpful for the less experienced readers.